(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2013)
The capital market is areal part of Indian economy. Thusly whatever the national and worldwideoccasions (regular and man acts) happened that they had an effect specificallyon the Indian economy and by implication on the capital markets of individualnations. The most recent occasions like, RBI’s credit policy rates on 26th July2011 and S&p’s evaluations on eighth August, 2011 on Us government validityare the major occasions which were influenced the Indian capital marketantagonistically. In this crossroads, an endeavor is made to survey the bankingsector’s cost patterns i.e. which bank stock costs got abundantly influencedand which are minimum influenced. This study will be of service to know thesuggestions of the occasions on stock costs and to make astute and normalventure decision.